Characterization and expression profiling of serine protease inhibitors in the diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae). (December 2017) - Lin, Hailan; Lin, Xijian; Zhu, Jiwei; Yu, Xiao-Qiang; Xia, Xiaofeng; Yao, Fengluan; Yang, Guang; You, Minsheng
Abstract Background Serine protease inhibitors (SPIs) have been found in all living organisms and play significant roles in digestion, development and innate immunity. In this study, we present a genome-wide identification and expression profiling of SPI genes in the diamondback moth, Plutella xylostella (L.), a major pest of cruciferous crops with global distribution and broad resistance to different types of insecticides. Results A total of 61 potential SPI genes were identified in theP. xylostella genome, and these SPIs were classified into serpins, canonical inhibitors, and alpha-2-macroglobulins based on their modes of action. Sequence alignments showed that amino acid residues in the hinge region of known inhibitory serpins from other insect species were conserved in mostP. xylostella serpins, suggesting that theseP. xylostella serpins may be functionally active. Phylogenetic analysis confirmed thatP. xylostella inhibitory serpins were clustered with known inhibitory serpins from six other insect species. More interestingly, nine serpins were highly similar to the orthologues inManduca sexta which have been demonstrated to participate in regulating the prophenoloxidase activation cascade, an important innate immune response in insects. Of the 61P.xylostella SPI genes, 33 were canonical SPIs containing seven types of inhibitor domains, including Kunitz, Kazal, TIL, amfpi, Antistasin, WAP and Pacifastin. Moreover, some SPIs contained additional non-inhibitor domains, including spondin_N, reeler, and other modules, which may be involved in protein-protein interactions. Gene expression profiling showed gene-differential, stage- and sex-specific expression patterns of SPIs, suggesting that SPIs may be involved in multiple physiological processes inP. xylostella . Conclusions This is the most comprehensive investigation so far on SPI genes inP. xylostella . The characterized features and expression patterns ofP. xylostell a SPIs indicate that the SPI family genes may be involved in innate immunity of this species. Our findings provide valuable information for uncovering further biological roles of SPI genes inP. xylostella .